Political Budgeting Dynamics: Executive-Legislative Interaction for COVID-19 Budget Policy in Indonesia and Singapore [Dinamika Politik Anggaran: Interaksi Eksekutif-Legislatif dalam Kebijakan Anggaran Penanganan COVID-19 di Indonesia dan Singapura] - Soeparno, Moh. Eddy D (Jurnal Politica, 2022)
This article will describe and analyze the political consensus process between executivelegislative regarding Covid-19 budgeting policy in Indonesia and Singapore. This article will mainly discuss the use of national reserve in Singapore and Government Regulation in the lie of Law (Perppu) No.1 of 2020 in Indonesia. This article uses New Institutionalism Approaches, Political Budgeting Theory, and Crisis Budget Theory to answer the research questions. This article finds that the Covid-19 pandemic has changed procedures, power distributions, incremental approaches, and conflict types for the Covid-19 budget policy process. In addition, the analysis of crisis budgeting policies, such as withdrawal of national reserves and issuance of a Perppu, shows that crisis conditions would encourage the emergence of shared interests and cooperation between executive-legislative institutions to protect their constituents from the threat of the Covid-19 pandemic. However, there are different types of cooperation incentives in those two countries. Singapore has the dominance of one political party that encourages executive-legislative cooperation, while Indonesia has a multi-party presidential system that encourages executive-legislative collaboration.This article finds that the political system model will have implications for the pattern of executive-legislative interaction in Covid-19 budget politics.AbstrakArtikel ini berusaha memberikan deskripsi dan analisa perbandingan tentang proses interaksi eksekutif-legislatif dalam pembentukan konsensus politik terkaitkebijakan anggaran penanganan Covid-19 di Indonesia dan Singapura, terutama pembahasan penggunaan national reserve (cadangan nasional) di Singapura dan penerbitan Perppu No.1 Tahun 2020 di Indonesia. Artikel ini menggunakan pendekatan Institusionalisme Baru, Teori Politik Anggaran, dan Teori Anggaran Krisis. Artikel ini menemukan bahwa Pandemi Covid-19 telah mengubah prosedur, distribusi kekuasaan, pendekatan inkremental, dan jenis konflik dalam proses kebijakan anggaran penanganan Covid-19. Selain itu, analisa politik anggaran dalam kebijakan anggaran krisis (penarikan national reserves dan penerbitan Perppu) memperlihatkan bahwa kondisi krisis akan mendorong kemunculan kesamaan kepentingan dan kerja sama antara lembaga eksekutif-legislatif untuk melindungi konstituennya dari ancaman Pandemi Covid-19. Namun, terdapat dorongan (insentif) yang berbeda dari kerja sama yang terbentuk antara eksekutif-legislatif di kedua negara tersebut. Singapura memiliki dominasi satu partai politik yang mendorong kerja sama eksekutif-legislatif, sedangkan Indonesia memiliki sistem Presidensialisme multi-partai yang mendorong kerja sama eksekutif-legislatif. Artikel ini menemukan bahwa model sistem politik akan berimplikasi pada pola interaksi eksekutif-legislatif dalam politik anggaran Covid-19.